In situ formation of electronically coupled superlattices of Cu1.1S nanodiscs at the liquid/air interface. Issue 33 (4th April 2019) - Maiti, Sonam; Maiti, Santanu; Maier, Andre; Banerjee, Rupak; Shen, Chen; Murphy, Bridget M.; Scheele, Marcus; Schreiber, Frank
Abstract : We report on the in situ monitoring of the formation of conductive superlattices of Cu1.1 S nanodiscs via cross-linking with semiconducting cobalt 4, 4′, 4′′, 4′′′-tetraaminophthalocyanine (CoTAPc) molecules at the liquid/air interface by real-time grazing incidence small angle X-ray scattering (GISAXS). Abstract : We report on the in situ monitoring of the formation of conductive superlattices of Cu1.1 S nanodiscs via cross-linking with semiconducting cobalt 4, 4′, 4′′, 4′′′-tetraaminophthalocyanine (CoTAPc) molecules at the liquid/air interface by real-time grazing incidence small angle X-ray scattering (GISAXS). We determine the structure, symmetry and lattice parameters of the superlattices, formed during solvent evaporation and ligand exchange on the self-assembled nanodiscs. Cu1.1 S nanodiscs self-assemble into a two-dimensional hexagonal superlattice with a minor in-plane contraction (∼0.2 nm) in the lattice parameter. A continuous contraction of the superlattice has been observed during ligand exchange, preserving the initial hexagonal symmetry. We estimate a resultant decrement of about 5% in the in-plane lattice parameters. The contraction is attributed to the continuous replacement of the native oleylamine surface ligands with rigid CoTAPc. The successful cross-linking of the nanodiscs is manifested in terms of the high electrical conductivity observed in the superlattices. This finding provides a convenient platform to understand the correlation between the structure and transport of the coupled superstructures of organic and inorganic nanocrystals of anisotropic shape.